2021
DOI: 10.1038/s41598-021-90507-w
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PARD3 predicts poor prognosis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most commonly cancers with poor prognosis and drug response. Identifying accurate therapeutic targets would facilitate precision treatment and prolong survival for HCC. In this study, we analyzed liver hepatocellular carcinoma (LIHC) RNA sequencing (RNA-seq) data from The Cancer Genome Atlas (TCGA), and identified PARD3 as one of the most significantly differentially expressed genes (DEGs). Then, we investigated the relationship between PARD3 and outcomes of HCC, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…1A). After quality control, a total of 72,128 cells (42,928 stage-I and 29,200 stage-II) were used for downstream analysis (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). After quality control, a total of 72,128 cells (42,928 stage-I and 29,200 stage-II) were used for downstream analysis (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The rst subtype, cluster 0 characterised by MS4A6A, CD163 and CD163L, had the phenotype of resident-like macrophage, thus it was referred to as C0-Res thereafter. A few marker genes of the cluster 1 were found to be associated with tumorigenesis, such as PARD3 [42], EGFR [43], and SMAD3 [44], was thus labelled as C1-TAM (Table S4). The third subtype showed the signi cant upregulation of the markers of M2-like MΦ, including SLC16A10 [45], SLC11A1 [46] and CTSL [47], and thus we named it C2-M2.…”
Section: Tumour In Ltrating Macrophages Of the CCII Patients Showed I...mentioning
confidence: 99%
“…DNA copy number and DNA methylation regulate HSPG2 expression in oligodendroglioma [39]. PARD3 is involved in a number of immunoinvasive levels and may be a potential prognostic biomarker and therapeutic target for hepatocellular carcinoma [40].…”
Section: Prediction Of Candidate Small-molecule Drugsmentioning
confidence: 99%
“…Also, activation of PARD3 signaling was associated with the increased autophagy activity and colorectal cancer cell proliferation [ 15 ]. It was found that PARD3 was overexpressed in HCC and associated with poor prognosis [ 16 ]. However, its role in HCC has not been reported.…”
Section: Introductionmentioning
confidence: 99%